Nonoperative management of acute epidural hematoma diagnosed by CT: the neuroradiologist's role. - Hamilton, M; Wallace, C (American Journal of Neuroradiology, 1992)
PURPOSE: To determine whether certain patients with epidural hematomas would benefit from conservative treatment and to assess the neuroradiologist's role in decision-making. METHODS: We reviewed the CT scan findings, clinical presentation and outcome of 48 consecutive patients with epidural hematoma managed at our institution within the past 5 years. In 18 patients, initial management was nonsurgical, and only one of these went on to require surgery due to clinical deterioration and evidence of enlargement of hematoma on CT. The remainder of these 18 did well without surgery. OBSERVATIONS AND CONCLUSIONS: Clinical indicators of neurologic dysfunction (decrease in Glasgow coma scale score, pupillary dilatation, and hemiparesis) in the presence of even small epidural hematomas usually dictates the need for surgical management. The role of the neuroradiologist is most important when the patient presents in a good clinical state, when identification of both favorable and unfavorable prognostic factors on Ct is essential. The initial diameter of nonsurgically managed epidural hematomas generally must be small (mean, 1.26 cm in our series, all under 1.5 cm), and midline shift should be minimal (mean, 1.8 mm in our series). The identification of lucent areas within the epidural hematoma (suggesting active bleeding), or CT evidence of uncal herniation, can be ominous and the neurosurgeon must be alerted to their presence. Even in the presence of a favorable clinical status, presence of a larger epidural hematoma with significant mass effect or central lucent areas should alert the neuroradiologist and neurosurgeon to the strong possibility of sudden neurologic deterioration, and indicate the probable need for surgical management.